Engineered chloroplast dsRNA silences cytochrome p450 monooxygenase, V‐ATPase and chitin synthase genes in the insect gut and disrupts Helicoverpa armigera larval development and pupation. Issue 3 (17th March 2015) - Jin, Shuangxia; Singh, Nameirakpam D.; Li, Lebin; Zhang, Xianlong; Daniell, Henry
Summary In the past two decades, chloroplast genetic engineering has been advanced to achieve high‐level protein accumulation but not for down‐regulation of targeted genes. Therefore, in this report, lepidopteran chitin synthase (Chi), cytochrome P450 monooxygenase (P450) and V‐ATPase dsRNAs were expressed via the chloroplast genome to study RNA interference (RNAi) of target genes in intended hosts. PCR and Southern blot analysis confirmed homoplasmy and site‐specific integration of transgene cassettes into the chloroplast genomes. Northern blots and real‐time qRT‐PCR confirmed abundant processed and unprocessed dsRNA transcripts (up to 3.45 million copies of P450 dsRNAs/μg total RNA); the abundance of cleaved dsRNA was greater than the endogenous psbA transcript. Feeding of leaves expressing P450, Chi and V‐ATPase dsRNA decreased transcription of the targeted gene to almost undetectable levels in the insect midgut, likely after further processing of dsRNA in their gut. Consequently, the net weight of larvae, growth and pupation rates were significantly reduced by chloroplast‐derived dsRNAs. Taken together, successful expression of dsRNAs via the chloroplast genome for the first time opens the door to study RNA interference/processing within plastids. Most importantly, dsRNA expressed in chloroplasts can be utilized for gene inactivation to confer desired agronomic traits or for various biomedical applications, including down‐regulation of dysfunctional genes in cancer or autoimmune disorders, after oral delivery of dsRNA bioencapsulated within plant cells.